Chronicles of the seige of Golkonda Fort : an abridged translation of the Waqāʼiʻ of Niʻmat Khanʼ ʻĀli - Naʻmat Ḵẖān-i-ʻĀlī, d. ca. 1710 (IAD oriental series ;, 1975)
History of the occupation of Golconda, Deccan, by Aurangzib, Emperor of Hindustan, 1619-1707.